ANALISIS EMPOWERING LEADERSHIP DAN PSYCHOLOGICAL EMPOWERMENT DALAM ORGANISASI - Mutamimah .; Munadharoh . (Department of Management, Faculty of Economics, Universitas Islam Sutan Agung, Semarang, 2013)
This study aims to describe and analyze the effect of empowering leadership on employee performance, empowering leadership on psychological empowerment, empowerment influence of role identity to strengthen the relationship between empowering leadership and psychological empowerment, psychological empowerment influences on creative engagement process, the influence of psychological empowerment on intristic motivation, leader influence encouragement of creativity in strengthening the relationship between psychological empowerment and creativeengagement process, the influence of the creative process on the performance of employee engagement, motivation intristic influence on employee performance. Population of this study are all employees of Sultan Agung Islamic Hospital. Samples method conducted by proportional sampling technique. Then the analytical techniques used Partial Least Square (PLS). Based on the hypothesis of this study can be concluded that: 1) Empowering leadership have positive and significant effect on employees performance, 2) Empowering leadership have positive effect but no significant effect on psychological empowerment, 3) Empowerment role identity significantly strengthen the positive relationship between empowering leadership andpsychological empowerment., 4) Psychological empowerment have positive influence but not significant to creative process engagement, 5) Psychological empowerment have positive and significant effect on instrinsic motivation., 6) Encouragement of creativity leader reinforces a significant positive effect between psychological empowerment and creative engagement process, 7) Creative process engagement have positive effect but not significant to employees performance, 8) Intrinsic motivation have positive and significant effect on employees performance.Keywords : Empowering leadership, empowerment role identity, leader encouragement of creativity, psychological empowerment, creative process engagement, intrinsicmotivation, kinerja karyawan.